A comparison of the efficiacy of three different cryotherapy treatments used in the athletic recovery of sportspeople - literature review - Kepiska, M.; Bednarek, J.; Szygula, Z.; Teleglów, A.; Dabrowski, Z. (Medicina Sportiva, 2013)
It has been assumed that cryotherapy treatments improve athletic recovery and prevent the negative effects of strain caused by training. Body response to low temperatures is reflected in many changes in the hormonal, blood, nervous and immune systems, which may significantly influence tissue regeneration mechanisms. The use of ice or other forms of local cooling is a popular method for the treatment of sports-related injuries. This method is widely used by athletes and allows for fast return to sports activities shortly after injury. The purpose of this paper was to compare the literature reports on three different cryotherapy treatments (ice massage, whole-body cryotherapy, and cold water immersion) and to demonstrate the efficacy of these methods in the athletic recovery